Efficacy of Apoptic Agents in Cervical Cancer Treatment - Esra İşçi Bostancı; Hacer İlke Önen (Gazi Medical Journal)
Cervical cancer is one of the prevalent gynecologic cancer in the world. Through the cancer development mechanism, it is well known that apoptosis is so important. Many of the studies investigate the relation between apoptosis and carcinogenesis and related to this treatment regimen also. In this review, we aimed to analyse new opportunities in cervical cancer treatment, in the light of the literature.